Design, synthesis and biological evaluation of buthutin derivatives as cardioprotective agents - Yuan Liu; Fa-Qi Wang; Xin-Hao Hua; Shu-Han Yang; Li-Ning Wang; Yun-Sheng Xu; Chen-Yue Shao; Xiang-Bo Gou; Yu-Ming Liu (Natural Products and Bioprospecting)
Abstract Natural products are the important sources in cardiovascular drug development. In this study, twenty-nine buthutin derivatives were designed, synthesized, and evaluated for their NHE-1 inhibition and protective effects on cardiomyocyte injury. The structure of the newly synthesized compounds had been confirmed by 1H-NMR, 13C-NMR, and HR-ESI-MS spectra. Among all target compounds at 1 μM, compounds 9d, 9f, 9k, 9m, and 9n, with a protection ratio exceeding 30%, exerted stronger protective effects on H9c2 cardiomyocyte than positive control dexrazoxane and buthutin A. Meanwhile, compounds 9k, 9m, and 9o showed the significant NHE-1 inhibitory activities on H9c2 cardiomyocyte, all with a dpHi/min value less than 0.23. What is more, compounds 9k, 9m, 9o and buthutin A all exhibited the specificity on NHE-1 inhibition. Molecular modelling studies suggested the ability of compounds 9m and 9o to establish interactions with three hydrogen bonds to Asp267 and Glu346 of NHE-1, but also the ability with much lower CDOCKER energies than positive control cariporide and buthutin A. The structure–activity relationship (SAR) studies suggested that the presences of amide group, four-carbon linker, and para hydroxyl benzene ring were advantageous pharmacophores for above two pharmacological actions. This research would open new avenues for developing amide-guanidine-based cardioprotective agents. Graphical Abstract